The First Description of the Microbial Diversity in the Amarillo River (La Rioja, Argentina), a Natural Extreme Environment Where the Whole Microbial Community Paints the Landscape Yellow - Cecilia Elena Bernardelli; Deborah Colman; Edgardo Ruben Donati; María Sofía Urbieta (Microorganisms, 2024)
The Amarillo River in Famatina, La Rioja, Argentina, is a natural acidic river with distinctive yellow-ochreous iron precipitates along its course. While mining activities have occurred in the area, the river’s natural acidity is influenced by environmental factors beyond mineralogy, where microbial species have a crucial role. Although iron-oxidising bacteria have been identified, a comprehensive analysis of the entire microbial community in this extreme environment has not yet been conducted. In this study, we employ high-throughput sequencing to explore the bacterial and fungal diversity in the Amarillo River and Cueva de Pérez terraces, considered prehistoric analogues of the current river basin. Fe(II)-enrichment cultures mimicking different environmental conditions of the river were also analysed to better understand the roles of prokaryotes and fungi in iron oxidation processes. Additionally, we investigate the ecological relationships between bacteria and fungi using co-occurrence and network analysis. Our findings reveal a diverse bacterial community in the river and terraces, including uncultured species affiliated with Acidimicrobiia, part of an uncharacterised universal microbial acidic diversity. Acidophiles such as Acidithiobacillus ferrivorans, the main iron oxidiser of the system, and Acidiphilium, which is unable to catalyse Fe(II) oxidation but has a great metabolic flexibility,, are part of the core of the microbial community, showing significant involvement in intraspecies interactions. Alicyclobacillus, which is the main Fe(II) oxidiser in the enrichment culture at 30 °C and is detected all over the system, highlights its flexibility towards the iron cycle. The prevalence of key microorganisms in both rivers and terraces implies their enduring contribution to the iron cycle as well as in shaping the iconic yellow landscape of the Amarillo River. In conclusion, this study enhances our understanding of microbial involvement in iron mineral precipitation, emphasising the collaborative efforts of bacteria and fungi as fundamental geological agents in the Amarillo River.